New development of Chinese Criminal law - Wang, Shizhou (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
After the Criminal Law of the People's Republic of China was promulgated in 1979 and revised in 1997, this Law was revised and supplemented by one separate supplementary decision, 11 Criminal Amendments and 14 Criminal Legislative Interpretations. In terms of content, the Criminal Amendments and Criminal Legislative Interpretations introduced in this article after 2010 reflect the new development of Criminal Law in China. This article explains the main forms and features of these new development. It outlines the legislative measures to abolish the death penalty and to implement the criminal policy of "combining leniency and strictness". It explains the new measures in the protection of national security and national dignity and in the fighting against terrorism and corruption. A summary is given to the new provisions in terms of protecting information network, citizens’ personal information, social integrity and public order, environment, financial order, intellectual property rights, minors, traffic safety, the safety of food and drugs. In addition, the issues heatedly debated in theoretical and practical fields are introduced on the age of criminal responsibility for minors, the trend of Chinese criminal legislation, the establishment of criminal law provisions (criminal constitution), and the implementation of criminal law. The author hopes that this article shall benefit the legal exchanges and mutual understanding between the people of Georgia and the People’s Republic of China.